STRENGTHENING SHARIA ECONOMIC FOUNDATIONS THROUGH EARLY FINANCIAL LITERACY AND MARKET INTEGRITY - Rahmayati, Rahmayati (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to strengthen the foundations of Sharia economics from an early age by evaluating, implementing, and the effects of implementing market integrity and financial literacy at the elementary school level to increase financial inclusion. The research approach uses qualitative methods involving interviews with educators, parents, and students, observations, and the use of secondary data. The results of this research can provide a comprehensive understanding of the extent to which financial literacy and market integrity influence elementary school students' economic knowledge. Sharia financial economics is used as a tool to improve financial welfare.